« C’est trahison de se marier sans s’espouser » – Montaigne et sa conception du mariage - Szeliga, Dorota (Studia Romanica Posnaniensia, 2011)
This article is an attempt to look into an issue, many times undertaken by critics, of Montaigne’s attitude towards marriage. Major reflections on the subject are described by the author of the Essays in the chapter « Upon some verses of Virgil » (III, 5). However, comments scattered around other places, often contradictory in their nature, create a picture full of ambiguities.